Application of Sanctions for Performers of Siri Marriage in the Fatwa MPU Aceh Number 1 of 2010 concerning Siri Marriage: Penerapan Sanksi Bagi Pelaku Nikah Siri Dalam Fatwa MPU Aceh Nomor 1 tahun 2010 Tentang Nikah Siri - Hanapi, Agustin; Mauliana, Sudjah (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2022)
Some society assumed that all person who perform marriages under the hands or unregistered marriages are marriages that are carried out secretly without the knowledge of official officers, namely mariages record officer. Unregistered marriages become a problem in the community that can’t stop it soon, more harm than good. Unregistered marriages can also have a big impact on the consequences of the marriages law there is especially an bad effect on women and children. Now a days much of all still many unregistered marriages processed, because there are still many unofficial marriages with decision of false judge, therefore need for applicate the sanctions for the two perpetrators of unregistered marriages, in this case teh MPU Aceh have the create Fatwa about this problem one, so they must state a regulation to protect this habitual can not occur again in our community. Therefore, the researcher is interested in reviewing the application of sanctions for unregistered marriages perpetrators in MPU Aceh Fatwa No. 1 of 2010 concerning Siri Marriages. The research methods used are field research and literature research. The result in this study state that MPU Aceh applied sanctions for perpetrators of this series of marriages against false judge with imprisonment, the presence of false judge this unregistered marriages is viral now, therefore there needs to be sanctions applied. In the study of Maqasid Syar’iyah the recording of marriages agreements falls into the category of primary benefits of Daruriyat that can protect and maintain the benefit of religion, soul, reason, offspring, and property. Related to offspring, because with the recording, for women children benefif from the wife gets an inheritance and the child gets.